Implementasi Perlindungan Peretasan Google In App Purchase dengan Metode One Time Server Side Verfication, Verification Bypass Detection, dan Obfuscator pada Aplikasi Informasi Cuaca Android - M Faizal Putra Pradana; Agi Putra Kharisma; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
In App Purchase System is one of Google Play's features that allows developers to sell additional contents on applications that available on Google Play. But the In App Purchase System has its shortcomings, it can be hacked by VirtualSwindler system. LuckyPatcher is an example of VirtualSwindler system that able to manipulate signature verification process and save unauthentic purchase data into the local device system. The combination of 3 security methods, Server Side Verification, Verification Bypass Detection, dan Obfuscator, successfuly secure the In App Purchase system of a Weather Information App from the attacks of LuckyPatcher with 100% of accuracies . Verification Bypass Detection will determine wether the verification process is authentic or not. Server Side Verification will check the authenticity of saved purchase data without the worries of being manipulated by the compromised In App Purchase system. Obsfucator can keep the saved data secure from unauthentic modifications.